Sistem Penentuan Prioritas Bantuan Masjid Kemenag Kanwil Provinsi Kalbar Dengan Metode WP - Renny Puspita Sari; Ulya Ainurrahim (Jurnal ICT: Information Communication & Technology, 2022)
Providing guidance, services, and assistance in the implementation of religious teachings and ensuring the welfare of the Indonesian people in carrying out worship. This is also the responsibility of the Indonesian government. Government support in facilitating community worship is to provide assistance for places of worship for each religion. One of them is the assistance program for mosques from the Ministry of Religion. It has a special budget every year to provide assistance to mosques throughout Indonesia. The life of the Islamic community cannot be separated from a mosque. This place has a big impact to help smooth the activities of the Muslim community. The mosque is a place of worship for the Muslim community, besides that, it also has other important aspects, namely social, educational, economic and others. So this study will raise a case regarding the Priority Decision Support System for mosque aid recipients by the Ministry of Religion of West Kalimantan Province. based on agreed criteria. By going through the Weighted Product method of prioritizing acceptance of mosque assistance does not require a long calculation time, and produces an objective and appropriate decision